Porous Electrospun Fibers as Optical Sensor for Metal Ion - Thidarat Pandhumas (Science Faculty of Chiang Mai University, 2019)
Electrospun fibers as Fe3+ optical sensor were prepared from poly(methyl methacrylate) (PMMA), poly(vinyl chloride-co-vinyl acetate-co-vinyl alcohol), pyrene, and poly(ethylene glycol) (PEG) as a water-soluble porogen. The effect of PEG content (0-40 wt.%) on fiber size and morphology was studied using scanning electron microscopy (SEM). Uniform and bead-free fibers were obtained from all PEG loadings. The average diameter of fibers without PEG was 2.79 mm. Fiber size increased upon incorporation of PEG, except for fibers from 20% PEG. Attenuated total reflection Fourier transform infrared spectroscopy (ATR-FTIR) analysis and thermogravimetric analysis confirmed a complete removal of PEG after 24 h of immersion in water. Porous structures were clearly observed for fibers from solutions with 30 and 40% PEG. Since fiber breakage was observed after water immersion in fibers from solution with 40% PEG, only porous fibers from solutions with 10, 20, and 30% PEG were tested toward Fe3+. Porous fibers from 30% PEG solution exhibited highest sensing performance with the ratio of fluorescence intensities before and after (F0/F) immersion into 1.0 mM Fe3+ solution of 1.31. In addition, the porous fibers showed highly sensitive and selective responses toward Fe3+ over other selected metal ions, and showed a good reversibility after two cycles of quenching and regeneration.